2020
DOI: 10.1111/1462-2920.14902
|View full text |Cite
|
Sign up to set email alerts
|

A diverse uncultivated microbial community is responsible for organic matter degradation in the Black Sea sulphidic zone

Abstract: Organic matter degradation in marine environments is essential for the recycling of nutrients, especially under conditions of anoxia where organic matter tends to accumulate. However, little is known about the diversity of the microbial communities responsible for the mineralization of organic matter in the absence of oxygen, as well as the factors controlling their activities. Here, we determined the active heterotrophic prokaryotic community in the sulphidic water column of the Black Sea, an ideal model syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(106 citation statements)
references
References 107 publications
13
92
0
1
Order By: Relevance
“…The present study, together with others from the same Black Sea [5,8] (bioproject PRJNA649215) and those recent ones from the Cariaco Basin in Venezuela [21,23] show a rst glimpse on the microbiome of anoxic marine water columns. The redoxclines of these habitats show a convergence of various metabolisms at a time, among which we encounter anoxygenic photosynthesis such as that one observed in Chlorobium phaeobacteroides [24], ammonia oxidation by Nitrosopumilus spp., chemolithotrophic metabolisms carried by Gammaproteobacteria such Ca.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present study, together with others from the same Black Sea [5,8] (bioproject PRJNA649215) and those recent ones from the Cariaco Basin in Venezuela [21,23] show a rst glimpse on the microbiome of anoxic marine water columns. The redoxclines of these habitats show a convergence of various metabolisms at a time, among which we encounter anoxygenic photosynthesis such as that one observed in Chlorobium phaeobacteroides [24], ammonia oxidation by Nitrosopumilus spp., chemolithotrophic metabolisms carried by Gammaproteobacteria such Ca.…”
Section: Discussionsupporting
confidence: 78%
“…Although a few studies have been carried out by metagenomics and metagenome-assembled genomes (MAGs) reconstruction, the information available in databases about this unique environment is scarce. A recent study showed for the rst time the microbial structure of the sul dic waters of 1000 m depth [5], mainly dominated by sulfate reducers (Desulfobacterota and Chloro exi classes such as Dehalococcoidia or Anaerolinea), associated DOM degraders (Marinimicrobia, Cloacimonetes) and streamlined uncultured taxa such as Omnitrophica, Parcubacteria or Woesearchaeota. At the genome level, Black Sea microbes remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Abundance of these organisms indicates that they may play an important ecological role. Thus, it was recently shown that Woesearchaeota and Patescibacteria form an important part of the protein-degrading microbial communities in the Black Sea anoxic waters ( Suominen et al, 2019 ). Moreover, due to a higher ratio of surface area to volume, small cell size facilitates nutrient uptake and increases the metabolic rate ( Savage et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the genomes of these microorganisms revealed their ability to utilize proteinaceous substrates (Pelletier et al, 2008), cellulose (Limam et al, 2014), and propionate (Nobu et al, 2015), as well as to form syntrophic associations with other microorganisms (Dyksma and Gallert, 2019). Cloacimonetes were revealed in various anaerobic ecosystems, including the Black Sea sulfide zone, where they were found to be responsible for degradation of dissolved organic matter (Suominen et al, 2019). The highest share of Cloacimonetes (8-13%) occurred at the depths below 7 m. The closest relatives have been found in the sediments of meromictic lakes and in Pacific hydrothermal vents.…”
Section: Anoxic Zonementioning
confidence: 99%
“…Another filter was directly stored at −80 °C for analysis of the in situ microbial community. Water column samples for nutrient and DNA analysis were collected as described in Sollai et al (2019) and Suominen et al (2020) [ 30 , 33 ].…”
Section: Methodsmentioning
confidence: 99%